Development of a robust Sn-Cu based lead-free solder paste - Rita Mohd Said (School of Materials Engineering, 2019)
This research concentrated on an evolution in lead-free Sn-Cu based solder paste properties for electrical and electronic application and high power electronic devices. The main purposes of this project are listed as the followings; to compare the thermal properties, printability and solderability of Sn-0.7Cu based solder paste with micro-alloying Ni (Sn-0.7Cu-0.05Ni solder), composite solder (Sn-0.7Cu-0.05Ni-1TiO2) and transient liquid phase soldering Sn-10Cu (TLPS SC10) solder paste; to investigate the as-reflowed microstructure evolution and its effect on mechanical properties of Sn-0.7Cu based solder paste with micro-alloying Ni (Sn-0.7Cu-0.05Ni solder), composite solder (Sn-0.7Cu-0.05Ni-1TiO2) and transient liquid phase soldering Sn-10Cu (TLPS SC10) solder paste; to study the effects of isothermal aging on the bulk solder microstructure, interfacial growth kinetic and mechanical behavior of Sn-0.7Cu based solder paste with micro-alloying Ni (Sn-0.7Cu-0.05Ni solder), composite solder (Sn-0.7Cu-0.05Ni-1TiO2) and transient liquid phase soldering Sn-10Cu (TLPS SC10) solder paste.